Analysis of Trends and Challenges in the Implementation of PjBL-ESD at the Secondary Education Level: A Systematic Literature Review - Garmita Febriani Widaningsih; Prasetyorini Djarot; Indarini Dwi Pursitasari (Lembaga Teewan Journal Solutions, 2026)
This systematic literature review investigates the trends and challenges of Project-Based Learning (PjBL) integrated with Education for Sustainable Development (ESD) at the Senior High School level from 2020 to 2025. Following PRISMA 2020 guidelines, the study synthesizes empirical data from Scopus, Web of Science, and Google Scholar through a four-stage process: identification, screening, eligibility, and inclusion. Results indicate a significant surge in PjBL-ESD studies since 2020, driven by the SDGs